Apresiasi Sastra dan Eksplorasi Diri Anak melalui Perlombaan antar Madrasah Diniyah di Desa Nambangrejo Sukorejo Ponorogo - Anni Zuhriyah; Lisma Meilia Wijayanti; Ahmad Kirom (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Organizing competitions is very important, both general competitions and religious competitions such as competitions between Madrasah Diniyah Because this competition can increase children's self-confidence, increase insight and serve as a means of channeling children's interests and talents and a forum for children's potential as a medium for evaluating each child's self This research was conducted qualitatively using a case study approach at a competition between Madrsah Diniyah in Nambangrejo Village, Sukorejo Ponorogo subdistrict.